Open Tibial Fracture Treatment in Argentina: Reoperation Rates Following Surgical Management. Issue 2 (22nd April 2022) - Garabano, Germán; MacKechnie, Madeline C.; Pereira, Sebastian; Brown, Kelsey; Flores, Michael J.; Pesciallo, Cesar A.; Miclau, Theodore; Bidolegui, Fernando; ,
Abstract : Background: The purposes of the present study were (1) to characterize open tibial fractures and their treatment in trauma centers located across different regions of Argentina and (2) to evaluate the rates of and indications for reoperation after the surgical treatment of such fractures. Methods: This retrospective multicenter study evaluated open tibial fractures in Argentina that were operatively treated by experienced orthopaedic trauma surgeon-members of the Argentine Association of Orthopedic Trauma (AATO) between January 2015 and June 2020. Data were collected from 13 hospital databases; 8 hospitals were designated as "interior, " and 5 hospitals were designated as "exterior." The study included 701 skeletally mature patients, all of whom had a minimum of 12 months of follow-up. Information was collected on patient demographics, injury pattern and mechanism, fracture classification, treatment modality, reoperation rates, time between definitive fixation and reoperation, and indications for reoperation. Results: Seventy-six percent of presenting injuries were the result of a high-energy mechanism. Intramedullary nailing represented the most common type of fixation (88%). One hundred and fifty patients (21%) required reoperation. Delayed union/nonunion was the most common indication for reoperation in patients who had been previously treated with intramedullary nail fixation (31%; 39 of 126), and infection was the most common indication for reoperation in patients who had been treated with plate fixation (43%; 3 of 7). The time between the injury and definitive fixation was significantly different between the interior and exterior trauma centers (13.8 versus 4.7 days; p < 0.001), as was the time between definitive fixation and reoperation (69.3 versus 25.2 days; p = 0.004). The reoperation rates for the interior and exterior trauma centers were similar (20% versus 24%; p = 0.2). Infection, delayed union/nonunion, and implant removal were the most common indications for reoperation across groups. Conclusions: An improved understanding of the factors that influence treatment may help to guide future areas for improvement, establish educational goals, and create additional nationwide guidelines for open tibial fracture treatment. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.